Association between physical limitations and working life exposure to carrying heavy loads assessed using a job-exposure matrix: CONSTANCES cohort. Issue 5 (4th July 2021) - Ngabirano, Laure; Fadel, Marc; Leclerc, Annette; Evanoff, Bradley A.; Dale, Ann Marie; d'Errico, Angelo; Roquelaure, Yves; Descatha, Alexis
Abstract: Introduction: Decline in physical performance with age varies among workers. We studied the association between lifetime exposure to carrying heavy loads and limitations in climbing stairs. Methods: We used data from the French CONSTANCES study. A biomechanical Job-Exposure Matrix (JEM) was combined with lifetime job histories to build a cumulative exposure score, and compared with reported limitations in climbing stairs using robust Poisson models, stratified by sex and educational level. Results: Of the 26, 255 subjects, 618 men and 1, 080 women reported difficulties in climbing stairs; this outcome was associated with cumulative exposure to carrying heavy loads: adjusted PR= 2.17 (1.75-2.73) for men, 1.50 (1.30-1.74) for women. The association was primarily seen among less educated subjects. Conclusion: Cumulative work exposure to carrying heavy loads across the working life was associated with physical limitations in climbing stairs among the less educated in both genders.